Direct Vinylation of Alcohols or Aldehydes Employing Alkynes as Vinyl Donors: A Ruthenium Catalyzed C-C Bond Forming Transfer Hydrogenation - Patman, Ryan L. (2009)
[Image: see text] Under the conditions of ruthenium catalyzed transfer hydrogenation, 2-butyne couples to benzylic and aliphatic alcohols 1a–1i to furnish allylic alcohols 2a–2i, constituting a direct C-H vinylation of alcohols employing alkynes as vinyl donors. Under related transfer hydrogenation conditions employing formic acid as terminal reductant, 2-butyne couples to aldehydes 4a, 4b, and 4e to furnish identical products of carbonyl vinylation 2a, 2b, and 2e. Thus, carbonyl vinylation is achieved from the alcohol or the aldehyde oxidation level in the absence of any stoichiometric metallic reagents. Nonsymmetric alkynes 6a–6c couple efficiently to aldehyde 4b to provide allylic alcohols 2m–2o as single regioisomers. Acetylenic aldehyde 7a engages in efficient intramolecular coupling to deliver cyclic allylic alcohol 8a.